New vacuum solar telescope and observations with high resolution - Liu, Zhong; Xu, Jun; Gu, Bo-Zhong; Wang, Sen; You, Jian-Qi; Shen, Long-Xiang; Lu, Ru-Wei; Jin, Zhen-Yu; Chen, Lin-Fei; Lou, Ke; Li, Zhi; Liu, Guang-Qian; et al. (Research in astronomy and astrophysics, 2014)
The New Vacuum Solar Telescope （NVST） is a one meter vacuum solar telescope that aims to observe fine structures on the Sun. The main goals of NVST are high resolution imaging and spectral observations, including measurements of the solar magnetic field. NVST is the primary ground-based facility used by the Chinese solar research community in this solar cycle. It is located by Fuxian Lake in southwest China, where the seeing is good enough to perform high resolution observations. We first introduce the general conditions at the Fuxian Solar Observatory and the primary science cases of NVST. Then, the basic structures of this telescope and instruments are described in detail. Finally, some typical high resolution data of the solar photosphere and chromosphere are also shown.